In vivo optogenetic tracing of functional corticocortical connections between motor forelimb areas - Hira, Riichiro; Ohkubo, Fuki; Tanaka, Yasuhiro R.; Masamizu, Yoshito; Augustine, George J.; Kasai, Haruo; Matsuzaki, Masanori (Frontiers in Neural Circuits, 2013)
Interactions between distinct motor cortical areas are essential for coordinated motor behaviors. In rodents, the motor cortical forelimb areas are divided into at least two distinct areas: the rostral forelimb area (RFA) and the caudal forelimb area (CFA). The RFA is thought to be an equivalent of the premotor cortex in primates, whereas the CFA is believed to be an equivalent of the primary motor cortex. Although reciprocal connections between the RFA and the CFA have been anatomically identified in rats, it is unknown whether there are functional connections between these areas that can induce postsynaptic spikes. In this study, we used an in vivo Channelrhodopsin-2 photostimulation method to trace the functional connections between the mouse RFA and CFA. Simultaneous electrical recordings were utilized to detect spiking activities induced by synaptic inputs originating from photostimulated areas. This method, in combination with anatomical tracing, demonstrated that the RFA receives strong functional projections from layer 2/3 and/or layer 5a, but not from layer 5b, of the CFA. Further, the CFA receives strong projections from layer 5b neurons of the RFA. The onset latency of electrical responses evoked in remote areas upon photostimulation of the other areas was approximately 10 ms, which is consistent with the synaptic connectivity between these areas. Our results suggest that neuronal activities in the RFA and the CFA during movements are formed through asymmetric reciprocal connections.